Ensuring The Legality of Implementation of The Rights of Consumed in Institutions For The Execution of Punishments in The Republic of Uzbekistan - Shodiev Abdukarim Abduxmonovich (International Journal on Orange Technologies, 2021)
In the article, based on the study of legal acts on the execution of criminal punishments in the Republic of Uzbekistan, as well as the analysis of the opinions of scientists, the provision of law and discipline in institutions for the execution of sentences was studied